Reliability and validity of the long-distance corridor walk among stroke survivors - Shamay S.M. Ng; Tai-Wa Liu; Jack C.Y, Chan; Irene C.W. Chan; Judy C.L. Chu; Henry C.H. Poon; Ashley L.Y. Poon; Cynthia Y.Y. Lai; Mimi M.Y. Tse (Journal of Rehabilitation Medicine, 2020)

(untitled)
Objective: To identify the psychometric properties of the Long-Distance Corridor Walk (LDCW) among community-dwelling stroke survivors. Design: Cross-sectional. Subjects: Twenty-five stroke survivors and 25 healthy older adults. Methods: The LDCW was administered to the 25 stroke survivors on 2 separate days with a 7-day interval. Fugl-Meyer Assessment for the Lower Extremities (FMA-LE), measurement of lower limb muscle strength, Berg Balance Scale (BBS), limit of stability (LOS), Narrow-Corridor Walk Test (NCWT), Timed Up and Go (TUG) test, and the Community Integration Measure—Cantonese version (CIM) were performed on one of the days. The healthy older adults completed the LDCW once, and the results were recorded by a random rater. Results: The LDCW showed excellent inter-rater reliability and test-retest reliability, and significant correlations with FMA-LE, BBS, TUG, and NCWT. A cut-off score of 127.5 m for the 2-min walk and 426.69 s for the 400-m walk distinguished stroke survivors from healthy older adults. The MDC in the LDCW in the 2-min walk and 400-m walk were 18.69 m and 121.43 s, respectively. Conclusion: The LDCW is a reliable clinical measurement tool for the assessment of advanced walking capacity in stroke survivors.